Settlement Type and Educational Effectiveness of Polish Schools on the Example of the Kujawsko-Pomorskie Voivoideship - Murawska, Iwona; Przyborowska, Beata; Kopińska, Violetta; Błajet, Piotr (Bulletin of Geography. Socio-economic Series, 2019)
The article presents and analyses data on the educational potential of schools in relation to settlement type in Poland. On the example of two types of schools – successful and requiring help – their distribution was shown in the Kujawsko-Pomorskie Voivodeship. For this purpose, data from the Educational Value Added (EVA) index for voivodeship schools were interpreted. On this basis, it was determined what type of school the branches represent, and then classification and analysis was made for the village/city and the number of inhabitants. The results show that the educational potential of rural schools is lower than that of schools in cities. The results were interpreted on the basis of theories of cultural reproduction, bearing in mind the importance of settlement type for the construction of cultural capital.